PKM2/STAT1-mediated PD-L1 upregulation on neutrophils during sepsis promotes neutrophil organ accumulation by serving an anti-apoptotic role - Yinjiaozhi Li; Ruoming Tan; Ranran Li; Rui Tian; Zhaojun Liu; Xiaoli Wang; Erzhen Chen; Tingting Pan; Hongping Qu (BMC, 2023)
Abstract Background Delayed neutrophil apoptosis during sepsis may impact neutrophil organ accumulation and tissue immune homeostasis. Elucidating the mechanisms underlying neutrophil apoptosis may help identify potential therapeutic targets. Glycolysis is critical to neutrophil activities during sepsis. However, the precise mechanisms through which glycolysis regulates neutrophil physiology remain under-explored, especially those involving the non-metabolic functions of glycolytic enzymes. In the present study, the impact of programmed death ligand-1 (PD-L1) on neutrophil apoptosis was explored. The regulatory effect of the glycolytic enzyme, pyruvate kinase M2 (PKM2), whose role in septic neutrophils remains unaddressed, on neutrophil PD-L1 expression was also explored. Methods Peripheral blood neutrophils were isolated from patients with sepsis and healthy controls. PD-L1 and PKM2 levels were determined by flow cytometry and Western blotting, respectively. Dimethyl sulfoxide (DMSO)-differentiated HL-60 cells were stimulated with lipopolysaccharide (LPS) as an in vitro simulation of septic neutrophils. Cell apoptosis was assessed by annexin V/propidium iodide (annexin V/PI) staining, as well as determination of protein levels of cleaved caspase-3 and myeloid cell leukemia-1 (Mcl-1) by Western blotting. An in vivo model of sepsis was constructed by intraperitoneal injection of LPS (5 mg/kg) for 16 h. Pulmonary and hepatic neutrophil infiltration was assessed by flow cytometry or immunohistochemistry. Results PD-L1 level was elevated on neutrophils under septic conditions. Administration of neutralizing antibodies against PD-L1 partially reversed the inhibitory effect of LPS on neutrophil apoptosis. Neutrophil infiltration into the lung and liver was also reduced in PD-L1−/− mice 16 h after sepsis induction. PKM2 was upregulated in septic neutrophils and promoted neutrophil PD-L1 expression both in vitro and in vivo. In addition, PKM2 nuclear translocation was increased after LPS stimulation, which promoted PD-L1 expression by directly interacting with and activating signal transducer and activator of transcription 1 (STAT1). Inhibition of PKM2 activity or STAT1 activation also led to increased neutrophil apoptosis. Conclusion In this study, a PKM2/STAT1-mediated upregulation of PD-L1 on neutrophils and the anti-apoptotic effect of upregulated PD-L1 on neutrophils during sepsis were identified, which may result in increased pulmonary and hepatic neutrophil accumulation. These findings suggest that PKM2 and PD-L1 could serve as potential therapeutic targets.